Bond Failure Mechanism of Fully Grouted Rock Bolts - Chen, Jianhang; Li, Yongliang; Zhang, Junwen (SpringerBriefs in applied sciences and technology, 2023)
The purpose of writing this book is to provide the latest research findings in ground control techniques in mining engineering, especially the rock bolting techniques. Since rock bolts are widely used in mining engineering and civil engineering, they are significant in guaranteeing the safety of underground openings. However, instability issues still occur with the rock bolting technique. Therefore, it is valuable to understand the exact load transfer mechanism of rock bolts. This book summarised the recent research work regarding rock bolting conducted by the authors. It is valuable for the readers to fully understand the reinforcing mechanism of fully grouted rock bolts. This book focuses on the bond failure mode of fully grouted rock bolts, which is the most widely encountered failure mode in rock bolting. Different investigation approaches are used in this book, including numerical simulation, analytical modelling and experimental tests. Therefore, this book conducts a comprehensive study to reveal the bond failure process of fully grouted rock bolts. Moreover, it reveals the corresponding bond failure mechanism. Therefore, it helps the reads to fully understand the bond failure mechanism of rock bolting. Moreover, it helps the readers to develop new approaches and methods to prevent failure of the rock bolting system. This is an open access book.